The Methodology of Sheikh ‘Abdul Hayye al-Fārūqī and His Contemporary Approach to His Urdu Exegesis “Dars-e Qurān”: A Critical Appreciation: منهج الشيخ عبد الحي الفاروقي وأسلوبه المعاصر من خلال تفسيره الأردوى "درس قرآن": دراسة وصفية نقدية - Abbas, Kaleem; Nadeem, Dr. Muhammad Tayyab; Farooq, Dr. Hafiz Shuaib (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Sheikh ‘Abd al-Hayye al-Fārūqī (1887-1965) was determined to address human beings through the oral lectures and the academic writings. According to him, a person cannot explain the religion and its significant features except through the Holy Qurān, and the entity of the Islamic movement cannot be established except by directly benefiting from the Holy Book which revealed to guide people. Therefore, Sheikh “Abdul Hayye al-Fārūqī (late) felt the need for an interpretation that includes clarification of Islamic rulings and beliefs with the explanation of the words of al-Qurān and their clarification of meanings in the easy Urdu language for the common people. “Dars-e Qurān” of al-Fārūqī seems a significant contribution to the Qurānic exegesis in Indo-Pak Sub-Continent in Urdu language and it needs to be explored in terms of its method and relevance to our times. This paper explores its contemporary relevance and analyzes with critical appreciation.